Additions to the history of Hungarian dental care and education from the 18th century to the 20th century - András Kóbor (Fogorvosi Szemle, 2022)
After the church ban, the surgical and dental care provided by the monastic medicine of the early Middle Ages was replaced by the service of the barbers, who traditionally worked as a barber-surgeons. After organising into the guilds formed in commercial hubs, the barbers managed patient care on the outskirts of villages and cities. In addition, marketplaces were used to remove teeth by the wandering barbers . Among the rural population, other professionals (herbwomen, oil sellers) were participating in pain relief and inflammation reduction. From the 13th century, the teaching of surgery was taken over by the secular schools (Paris), thus establishing a branch of scholastic medicine. In Hungary, the university training for the surgeons, and thereafter, the dentists started at the University of Trnava, (Nagyszombat), and later, moved to Buda and Pest. Subsequently, a royal decree banned surgical and dental activities of barbers. For a long time, in Hungary, until the start of the university education in dentistry and training for dental doctors in the middle of the 19th century, it were wanderer surgeons and dentists who provided patient care to the population of the countryside.